Jessica McGovern - Thesis submitted in partial fulfilment of the degree of Doctor of Clinical Psychology (DClinPsych) - McGovern, J (2024)
Systematic Review of Research Literature (SRL) Secondary School-based, Cognitive-Behavioural Interventions to Enhance Positive Self-Concept in Adolescents At-Risk of Mental Health Difficulties: A Systematic Review of Randomised Controlled Trials